Bio-Based Coatings on Cellulosic Materials Resistant to Humidity and Fats - Guarda-Moraga, A; Bruna-Bugueno, J (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Cellulose stands out as a promising alternative to conventional polymers in food packaging due to its abundance, renewability, biodegradability and structural robustness. Despite these advantages, its natural low resistance to water and fats limits its direct application, necessitating the use of protective coatings to enhance its functionality. In this context, the use of biopolymeric coatings such as poly(lactic acid) (PLA), starch, lignin, chitin and chitosan has emerged as a sustainable solution, providing effective barriers against moisture and oils. These coatings not only improve the functional performance of cellulosic substrates but also reduce reliance on fossil-based plastics, fostering compostable systems and supporting a circular economy. This review analyzes recent developments in biopolymer-coated cellulosic packaging materials, focusing on their resistance to water and fats. The aim is to assess their potential for sustainable food packaging applications. The findings highlight how these innovations contribute to global sustainability goals, such as reducing plastic waste, lowering carbon emissions, and decreasing dependence on non-renewable resources. © 2025 by the authors.